Revealing the Role of Mobile Phase Composition and pH in Benzoic Acid Analysis of Beverages and Processed Foods: Implications for SDG 3 - Meyliana Wulandari; Galuh Fathin Aulia; Susy Affrini Hutapea; Mardiana Saaid; Vida Zenitha Sudariasri (Program Studi Kimia Universitas Negeri Jakarta, 2026)
To prevent health risks in excessive consumption, monitoring benzoic acid as a food additive is necessary in line with SDG 3 principles. Conventional methods for determining benzoic acid levels have limitations in selectivity and sensitivity due to matrix interference contained in food products. This study aims to determine benzoic acid levels in support of food safety monitoring in Jakarta by optimizing the mobile phase in a reversed-phase HPLC system (RP-HPLC. Reverse-phase high-performance liquid chromatography with a UV detector, investigated in this research, operated at 225 nm. A C-18 or octadecyl silica (ODS) column stationary phase (250 mm x 4,6 mm, 5 µm particle size) was used, which is classified as nonpolar. The mobile phase used is a polar methanol-phosphate buffer with a ratio 4:96 at pH 6.8. Optimization of mobile phase composition and pH was necessary to control the ionization degree of benzoic acid, improve analyte‒stationary phase interactions, and produce optimal retention time, peak shape, and resolution. The test results for benzoic acid levels in carbonated drinks, jelly drinks, and mayonnaise were 140.973 mg/kg, 232.294 mg/kg, and 710.695 mg/kg, respectively. It can be concluded that the benzoic acid levels in the sample remain below the maximum limit set by BPOM RI.